Measuring residential segregation in urban Mexico: Levels and patterns - Paavo Monkkonen (University of California, Institute of Urban and Regional Development (IURD), 2010)
Changing patterns of urban development in Latin America have drawn increasing attention to residential segregation, yet systematic quantitative analysis remains limited. Using data from the Mexican census of 2000, this paper describes spatial patterns and levels of segregation by ethnicity and socioeconomic status in over 100 cities. Findings confirm many recognized patterns; low-income and informally employed households tend to live in peripheral areas of the city, while high-income and formally employed households are more centrally concentrated. High-income areas are more socioeconomically diverse and densely developed than low-income areas. Indigenous people experience similar patterns of segregation at higher levels than do lowincome households. The difference in levels of segregation by income in cities of different sizes is statistically significant; larger cities are more segregated. Regional differences in patterns of segregation are also statistically significant and large, demonstrating the importance of both historical periods of urban development and levels of regional economic development.
Keywords: 330